2016
DOI: 10.1111/wej.12224
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of energy dissipation and flow regime over various forms of stepped spillways

Abstract: The efficient operation of reservoirs relies on the effective release of water during flooding, requiring a good understanding of spillways and their hydraulics. A series of experiments was conducted in a laboratory flume on a stepped spillway model with moderate slope (26.68) for discharges up to 0.0121 m 3 /s. Using regular uniform horizontal steps of 5 cm height, then several new step configurations including inclined and horizontal curved steps with and without reflector blocks, the flow patterns were inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 13 publications
3
18
0
7
Order By: Relevance
“…Guenther et al [12] studied the characteristics of aeration concentration, vortex characteristics, and energy dissipation rate with four different types of stepped spillways by model tests. Mero et al [13] suggested that the energy dissipation rate of both the upturned stepped body and the stepped horizontal plane were about twice that of the conventional body using model experiment. Barani et al [14] found that the shape of the step has a significant influence on the energy dissipation rate of the spillway by using three different types of texts: Conventional, upswing, and cantilever step.…”
Section: Of 11mentioning
confidence: 99%
“…Guenther et al [12] studied the characteristics of aeration concentration, vortex characteristics, and energy dissipation rate with four different types of stepped spillways by model tests. Mero et al [13] suggested that the energy dissipation rate of both the upturned stepped body and the stepped horizontal plane were about twice that of the conventional body using model experiment. Barani et al [14] found that the shape of the step has a significant influence on the energy dissipation rate of the spillway by using three different types of texts: Conventional, upswing, and cantilever step.…”
Section: Of 11mentioning
confidence: 99%
“…Sayısal çalışmanın doğrulanması için kullanılan deneysel çalışmadaki (Mero & Mitchell, 2017) modelin yüksekliği 0,25 m ve genişliği 0,296 m'dir. Toplamda beş basamaktan oluşan savağın her bir basamağının yüksekliği 0,05 m ve genişliği 0,10 m olmak üzere kanal açısı 26,6°'dir (Şekil 1).…”
Section: Geometrik Modelunclassified
“…Akım değerleri çok daha erken zamanda stabil hale gelmesine rağmen bütün modeller için analizler 10 saniye boyunca devam ettirilmiştir. Çalışmada (Mero & Mitchell, 2017) kullanılan hidrolik karakteristikler Tablo 1'de gösterilmiştir.…”
Section: Tarafından Tasarlanan Model Geometrisiunclassified
See 1 more Smart Citation
“…For example, Shahheydari et al (2014) showed a correlation between flow coefficient and energy dissipation and they showed that when the flow coefficient increases, energy dissipation decreases. Several researches have been carried out in a laboratory flume for the horizontal steps and the obtained results were compared with inclined and flat curve steps which decreased energy almost double more than horizontal steps (Mero and Mitchell, 2017).Over-flow, through-flow and under-flow breakers were considered to assess their effects on energy decrease. Comparison of the results showed that using the stepped spillway which has breakers, the energy reduction increased in comparison with the classical stepped spillway (Aal et al, 2017).…”
Section: Construction Cost Minimisation Of the Stepped Spillway Usingmentioning
confidence: 99%